2012
DOI: 10.1093/chromsci/bms167
|View full text |Cite
|
Sign up to set email alerts
|

RP-HPLC/Pre-Column Derivatization for Analysis of Omeprazole, Tinidazole, Doxycycline and Clarithromycin

Abstract: A validated, reliable and accurate reversed-phase high performance liquid chromatographic method using pre-column derivatization was adopted for the simultaneous determination of two ternary mixtures containing omeprazole, tinidazole and doxycycline hyclate or clarithromycin. Separation was achieved on a C18 column, through a gradient elution system using acetonitrile-methanol-water adjusted to pH = 6.60. Drugs were detected at 277 nm over concentration ranges of 1-112, 5-125, 2.5-550 and 2.5-100 µg/mL for ome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…In the majority of cases, sample preparation for the determination of tet racycline antibiotics in pharmaceuticals consists in the grinding of a sample and its dissolution in twice dis tilled water [116], 0.01 M HCl [117][118][119][120], a citrate buffer solution [121], a Britton-Robinson buffer solu tion [122], or a mixture of this buffer solution (pH 2.0) with acetonitrile (70 : 30) [123]. For the intensification of sample preparation, dissolution is sometimes per formed in an ultrasonic bath [116,118,121,123,124].…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the majority of cases, sample preparation for the determination of tet racycline antibiotics in pharmaceuticals consists in the grinding of a sample and its dissolution in twice dis tilled water [116], 0.01 M HCl [117][118][119][120], a citrate buffer solution [121], a Britton-Robinson buffer solu tion [122], or a mixture of this buffer solution (pH 2.0) with acetonitrile (70 : 30) [123]. For the intensification of sample preparation, dissolution is sometimes per formed in an ultrasonic bath [116,118,121,123,124].…”
Section: Sample Preparationmentioning
confidence: 99%
“…Photometric UV [23,51,53,60,73,74,80,81,89,113,124,134], diode array [15,19,22,29,37,55,68,72,84,86,138,139], and fluorescence [34,58,71,83,93,94] detectors are used for the detection of tetracy cline antibiotics. The number of works regarding the determination of tetracycline antibiotics by the HPLC with a mass spectrometric detector noticeably increased [15,21,27,32,35,69,100,105,106,112,114].…”
Section: Ms-dart [157]mentioning
confidence: 99%
“…Polymers have been extensively studied for the development of drug sensors based on their high conductivity, fast response times, and room temperature operation. The review of literature revealed that a few methods have been explored for the detection of TNZ, which includes titrimetric, 51 TLC, 52 spectrophotometric, [53][54][55] HPLC, 56 RP-HPLC 57,58 , and UV-visible spectrophotometry. [45][46][47][48] Tinidazole (TNZ), chemically 1-(2-ethyl sulfonyl ethyl)-2-methyl-5-nitroimidozole [A] is an antiparasitic drug used against protozoan infection including giardiasis, amoebiasis, and vaginal trichomoniasis.…”
Section: Introductionmentioning
confidence: 99%
“…Tinidazole was estimated in body fluids and in pharmaceutical formulations by spectrophotometry [24][25][26][27][28][29], potentiometry [29], HPLC methods [29][30][31], polarography [32,33] and resonance light scattering technique [34]. Clarithromycin has been reported to be estimated in body fluids and in pharmaceutical formulations by spectrophotometry [35], HPLC methods [36][37][38][39][40][41][42][43][44]. Omeprazole, Tinidazole and Clarithromycin were simultaneously determined by spectrophotometry [45,46].…”
Section: Introductionmentioning
confidence: 99%